Proprioception plays a different role for sensorimotor adaptation to different distortions - Bock, Otmar; Thomas, Monika (Human movement science, 2011)
If proprioceptive feedback is degraded by agonist–antagonist muscle vibration, then adaptation to rotated vision remains intact while adaptation to a velocity-dependent force field worsens. Here we evaluate whether this differential effect of vibration is related to the physical nature of the distortion – visual versus mechanical – or to their kinematic coupling to the subjects’ hand – velocity versus position dependent. Subjects adapted to a velocity-dependent visual distortion, to a position-dependent force, or to a velocity-dependent force; one half of the subjects adapted with, and the other half without agonist–antagonist vibration at the wrist, elbow, and shoulder. We found, as before, that vibration slowed down adaptation to a velocity-dependent force. However, vibration did not modify adaptation to the other two distortions, nor did it influence the aftereffects of any distortion. From this we conclude that intact proprioception supports strategic compensatory processes when proprioceptive signals agree with visual ones, and provide relevant (dynamic) information not available to the visual system.